2011
DOI: 10.1088/2041-8205/740/2/l50
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Negative Effective Magnetic Pressure Instability in Turbulence Simulations

Abstract: We present the first demonstration of the negative effective magnetic pressure instability in direct numerical simulations of stably stratified, externally forced, isothermal hydromagnetic turbulence in the regime of large plasma beta. By the action of this instability, an initially uniform horizontal magnetic field forms flux concentrations whose scale is large compared to the turbulent scale. We further show that the magnetic energy of these large-scale structures is only weakly dependent on the magnetic Rey… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
103
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(108 citation statements)
references
References 20 publications
5
103
0
Order By: Relevance
“…Direct numerical simulations (DNS) of Brandenburg et al (2011a) have shown in surprising detail many aspects of NEMPI that were previously seen in mean-field simulations (MFS) of Brandenburg et al (2010) and that have been anticipated based on analytical studies for some time (Kleeorin et al 1989(Kleeorin et al , 1990(Kleeorin et al , 1993(Kleeorin et al , 1996Kleeorin & Rogachevskii 1994;Rogachevskii & Kleeorin 2007).…”
Section: Introductionmentioning
confidence: 72%
“…Direct numerical simulations (DNS) of Brandenburg et al (2011a) have shown in surprising detail many aspects of NEMPI that were previously seen in mean-field simulations (MFS) of Brandenburg et al (2010) and that have been anticipated based on analytical studies for some time (Kleeorin et al 1989(Kleeorin et al , 1990(Kleeorin et al , 1993(Kleeorin et al , 1996Kleeorin & Rogachevskii 1994;Rogachevskii & Kleeorin 2007).…”
Section: Introductionmentioning
confidence: 72%
“…Brandenburg et al 2010Brandenburg et al , 2012Kemel et al 2012b;Käpylä et al 2012a, and references therein). Further numerical studies have confirmed the existence of NEMPI in direct numerical simulations (DNS) of forced turbulence with weak imposed horizontal (Brandenburg et al 2011) and vertical ) magnetic fields, and in a two-layer system with an upper unforced coronal layer and a lower forced layer (Warnecke et al 2013(Warnecke et al , 2016. With NEMPI, even uniform, sub-equipartition magnetic fields can lead to flux concentrations if there is sufficient scale separation between the forcing scale and the size of the domain in highly stratified turbulence.…”
Section: Introductionmentioning
confidence: 86%
“…The origin of such a field could be, e.g., an αΩ-type dynamo (Warnecke et al 2014). When NEMPI was excited, magnetic field concentrations were best detected in averages taken along the direction of the imposed field (Brandenburg et al 2011;Kemel et al 2012aKemel et al , 2013 if the scale separation between forcing scale and the size of the box is smaller than 30. We show two such cases for Runs A3h and C1h with the lowest and highest stratifications in Figs.…”
Section: Imposed Horizontal Fieldmentioning
confidence: 99%
“…We also compare our MFS results with those of DNS (Brandenburg et al 2011;Kemel et al 2013) using a similar polytropic setup. The governing equations for the mean quantities (denoted by an overbar) are fairly similar to those for the original equations, except that in the MFS viscosity and magnetic diffusivity are replaced by their turbulent counterparts, and the mean Lorentz force is supplemented by a parameterization of the turbulent contribution to the effective magnetic pressure.…”
Section: Mean-field Equationsmentioning
confidence: 99%